ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN USAHA KOPERASI DI KABUPATEN ROKAN HILIR Analysis Of Factors Affecting Financial Performance Of Business Cooperation In Rokan Hilir - Herlin, Darsi; Tanjung, Amries Rusli; Savitri, Enni (Jurnal Tepak Manajemen Bisnis, 2017)
The purpose of this study is to determine whether or not the amount of number of member, internal capital, external capital, bussiness volume, total asset in partially would affect the financial performances in Rokan Hilir Regency. The sample of the stuydy are Cooperatives annual meeting in the year of 2015 That is as much as 119 cooperative. By using a model multiple regression analysis. Conclusions based on the results of studies suggest that external capital, bussiness volume, and Total Asset affect the financial performance (SHU) in Rokan Hilir, while the Number of Member, Internal Capital has no effect on the financial performance (SHU) Cooperative in Rokan Hilir.